Measurement of the tt[bar]Z and tt[bar] W production cross sections in multilepton final states using 3.2 fb−1 of pp collisions at √s = 13 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (The European physical journal. C, Particles and fields, 2017)
A measurement of the tt¯Z and tt¯W production cross sections in final states with either two same-charge muons, or three or four leptons (electrons or muons) is presented. The analysis uses a data sample of proton–proton collisions at s√=13 TeV recorded with the ATLAS detector at the Large Hadron Collider in 2015, corresponding to a total integrated luminosity of 3.2 fb−1. The inclusive cross sections are extracted using likelihood fits to signal and control regions, resulting in σtt¯Z=0.9±0.3 pb and σtt¯W=1.5±0.8 pb, in agreement with the Standard Model predictions.
Gesehen am 31.01.2020
Im Titel steht der Buchstabe "s" unter dem Wurzelzeichen
Im Titel ist "-1" hochgestellt
Im Titel steht jeweils der 2. Buchstabe t mit einem Oberstrich
*ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, J.J. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, V. Radescu, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2828 weitere Personen]